Good Corporate Governance dan Kinerja Finansial Bank: Studi Empiris pada Emiten Perbankan di BEI (2021–2023) - Muhammad Irgi Sepri Saswandi; Syarbini Ikhsan; Rusliyawati Rusliyawati (Pusat Riset dan Inovasi Nasional, 2025)
This study is intended to examine the influence of Good Corporate Governance (GCG) practices on the financial outcomes of banks listed on the IDX throughout the 2021–2023 timeframe. GCG is measured using three main indicators: the presence of an audit committee, the proportion of independent commissioners, and institutional ownership. Financial performance is proxied by Return on Equity (ROE). A quantitative approach and explanatory research method are employed, with data collected through purposive sampling from 47 banks that meet the selection criteria. Testing between variables was conducted using multiple linear regression analysis techniques. The results reveal that the proportion of independent commissioners has a significant positive impact on ROE, while institutional ownership exerts a significant negative influence. Meanwhile, the audit committee variable does not have a statistically significant effect on financial performance. These findings reinforce the relevance of agency theory in the context of corporate oversight and accountability. They also highlight the importance of ownership structure and independent supervision in enhancing the efficiency of equity capital utilization. This research provides practical implications for bank management, regulators, and stakeholders in formulating more effective GCG policies aimed at promoting sustainable financial performance in Indonesia’s banking sector.